JISMONIY MADANIYAT FAKULTETI TALABALARINING TABIIY - ILMIY SIKL FANLARI BO‘YICHA MATEMATIK KOMPETENSIYALARINI TADQIQ QILISH - Yuldasheva, N.E. (SCIENCE and SOCIETY, 2022)
The article presents the results of a sociological survey conducted among the contingent of students of the Faculty of Physical Education and aimed at determining the mathematical abilities of future specialists working in the school education system.
Keywords: mathematical competence; interdisciplinary communication; level of formation; pedagogical test; natural sciences; professional knowledge; question-answer; indifference (indifference) and situational dependence